2019
DOI: 10.1002/pits.22229
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' self‐efficacy in bullying interventions and their probability of intervention

Abstract: Teacher intervention is an important factor in stopping bullying. Several studies indicate that teachers who believe they are capable of stopping bullying intervene more often in bullying. But this finding has only been based on hypothetical situations. It remains unclear if these results can be replicated in bullying interventions that the teachers actually performed. In addition, some studies claim that self‐efficacy is only connected to teacher intervention in direct forms of bullying, rather than indirect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 39 publications
1
36
0
2
Order By: Relevance
“…Teachers must manage the behavioural climate in classrooms (Farmer et al, 2011), and efficacious teachers can successfully oversee and influence this ecology (Hendrickx et al, 2017a). Teachers' Self-Efficacy (TSE) for intervening in social dynamics refers to the self-perceived ability of teachers to effectively manage and intervene in social behaviour and relationships (Bandura, 1977;Fischer & Bilz, 2019;Vieluf et al, 2013), including handling bullying situations (van Verseveld et al, 2019). Self-efficacy can be seen as a predictor of teachers' behaviour and actions (van Verseveld et al, 2019;Zee & Koomen, 2016).…”
Section: Teachers' Self-efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Teachers must manage the behavioural climate in classrooms (Farmer et al, 2011), and efficacious teachers can successfully oversee and influence this ecology (Hendrickx et al, 2017a). Teachers' Self-Efficacy (TSE) for intervening in social dynamics refers to the self-perceived ability of teachers to effectively manage and intervene in social behaviour and relationships (Bandura, 1977;Fischer & Bilz, 2019;Vieluf et al, 2013), including handling bullying situations (van Verseveld et al, 2019). Self-efficacy can be seen as a predictor of teachers' behaviour and actions (van Verseveld et al, 2019;Zee & Koomen, 2016).…”
Section: Teachers' Self-efficacymentioning
confidence: 99%
“…The teachers' role can take multiple forms. At the classroom level, teachers need to be able to manage the classroom and intervene in social dynamics (Fischer & Bilz, 2019). At the dyadic level, the relationship between teachers and students can provide students with signals about their teachers' approval and support, which can result in differences in children's social adaptation to school (Doumen et al, 2011) and function as a protective factor against peer victimization and its negative effects on students' self-esteem (Sulkowski & Simmons, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Among those, teachers’ self-efficacy assumes a central role. Literature showed that teachers with higher self-efficacy are more likely to intervene both for direct and indirect forms of bullying (Fischer and Bilz, 2019). Overall, higher levels of teachers’ self-efficacy increase the likelihood to identify victims and to understand the victims’ sufferance (Oldenburg et al, 2015; Nappa et al, 2018), increase the efforts teachers put in the intervention, and the success of those actions (Hawley and Williford, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Öğrencilere yönelik girişimlerde öz-saygı (Huitsing vd., 2019), öz-yeterlilik becerisini geliştirme (Fischer ve Bilz, 2019), empati (Doane vd., 2016), zorbalık davranışını önleme (Cross vd., 2016) gibi davranış geliştirmeye yönelik girişimler amaçlanmıştır. Öğretmenlere yönelik girişimlerde farkındalık (Wo'jcik ve Hełka, 2019), zorbalık davranışına müdahale etme ve ailelerle iş birliği içerisinde (Van Niejenhuisi vd., 2020) olamaya yönelik girişimler hedeflenmiştir.…”
Section: Uygulanan Girişimlerunclassified